(untitled) (Sains Humanika, 2014)
A total of 79 mothers of children with autism spectrum disorder (ASD) who were born within the period of 1998 to 2008 in Malaysia, were selected to answer the questionnaire in this study. The Childhood Autism Rating Scale (CARS) was adapted for parents (CARS-P) to assess the degree of autistic symptoms perceived by mothers. Difficulty in learning to speak was the first symptom found by most of mothers (above 60%). The binary logical regression result found the higher CARS-P score (severity of autistic symptom perceived by mothers) as predictor of the higher probability on early diagnosis of ASD under the age of 24 months. Larger samples are suggested in future study.